Fitness a lifetime commitment - Miller, David K. (David Keith) (Allyn and Bacon, 1995)
From providing instruction in evaluating their current level of fitness, to showing students how to design a personalized exercise program, this book identifies and explains health fitness problems and describes how an active lifestyle and good nutrition can help prevent or alleviate them. Strategies and guidelines for change in lifestyle and achievement of health fitness are integrated throughout the book.